2016
DOI: 10.3758/s13415-016-0466-8
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of happy mood on performance monitoring: Insights from error-related brain potentials

Abstract: Goal adaptive behavior requires the rapid detection of conflicts between actions and intentions or goals.While many studies have focused in the past on the influence of negative affect on this cognitive control process (and more specifically, on error monitoring), little is known about possible modulatory effects of positive affect on it. To address this question, we used a standard (positive) mood induction procedure (based on guided imagery) and asked participants to carry out a speeded Go/NoGo task, while h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 120 publications
(149 reference statements)
9
28
0
Order By: Relevance
“…In fact, the two components reflect relatively independent subprocesses in error processing: the ERN indicates fast detection of a mismatch between the correct response and actual response, and the Pe is related to more subjective evaluation of error response. In addition, researchers have found that the Pe is more sensitive to situation‐specific emotional processing (Koban & Pourtois, ; Paul, Walentowska, Bakic, Dondaine, & Pourtois, ). Since psychological stress generally results in complex emotional states, such as nervousness, anxiety, and restlessness (Dickerson & Kemeny, ), we expect that the negative emotional state would affect individuals’ error processing in later stages.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the two components reflect relatively independent subprocesses in error processing: the ERN indicates fast detection of a mismatch between the correct response and actual response, and the Pe is related to more subjective evaluation of error response. In addition, researchers have found that the Pe is more sensitive to situation‐specific emotional processing (Koban & Pourtois, ; Paul, Walentowska, Bakic, Dondaine, & Pourtois, ). Since psychological stress generally results in complex emotional states, such as nervousness, anxiety, and restlessness (Dickerson & Kemeny, ), we expect that the negative emotional state would affect individuals’ error processing in later stages.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, negative emotion states narrow attentional scope (Whitmer & Gotlib, 2013) and focus processing on fine-grained or local details (Bodenhausen, Gabriel, & Lineberger, 2000;Gasper & Clore, 2002), which may improve memory for central information (Kensinger, 2009). Further, negative emotion states compared to positive or neutral emotion improve reaction times, accuracy, and conscious error monitoring on several speeded choice tasks (Paul, Walentowska, Bakic, Dondaine, & Pourtois, 2017;Wiswede, Münte, & Rüsseler, 2009) and reduced susceptibility to encode false memories (Storbeck, & Clore, 2005) or incorporate false information into memory (Schmidt, Rosga, Schatto, Breidenstein, & Schwabe, 2014) may also stimulate critical thinking (Johnson & Johnson, 2009;Murphy, 2003) (for a review, see Forgas, 2013).…”
Section: Emotional Content and Memory Processesmentioning
confidence: 99%
“…This result suggests the existence of a mood incongruency effect, whereby the phasic and transient signal elicited by errors is temporarily augmented with happy mood, probably to timely signal their mismatching properties. In comparison, when response errors take place in a task context devoid of learning, such as during a standard interference task, the modulatory effect of positive mood on EM is notably different (Paul et al, 2016). In this context, response errors usually correspond to lapses of attention or concentration (Weissman, Roberts, Visscher, & Woldorff, 2006) and hence they likely acquire a different meaning than response errors committed during learning (Bakic et al, in press).…”
Section: Error Monitoringmentioning
confidence: 99%
“…In this situation, positive mood appears to decrease the (otherwise enhanced) motivational significance of response errors (at the Pe level selectively, while leaving the early ERN unchanged), consistent with a lowered processing of internal information (see Figure 1). Presumably, in order to preserve the benefits associated with the experience of positive mood, it is probably useful to transiently downplay the motivational significance of these worse than expected events in order to avoid jeopardizing the positive mood state (Paul et al, 2016). Alternatively, positive mood might make response errors (which are presumably negatively connoted) "loom" to a larger extent than neutral mood, when they conflict with the current mood state (hence creating a contrast effect during learning), while in other situations or contexts (when simple cognitive control tasks are used), it might conversely make them less salient by means of assimilation or regulation (Bless & Schwartz, 2010).…”
Section: Error Monitoringmentioning
confidence: 99%